Mergers of agrifood cooperatives and their effects: from expectations to results. An empirical study in four Spanish Autonomous Regions - Meliá, E.; Juliá, J. F.; Martínez, A. (Spanish Journal of Agricultural Research, 2010)
Mergers have become the most widely accepted formula for business growth among many different sectors. However, these processes do not always contribute to obtaining the expected results, particularly from an economic viewpoint. In light of these reflections, this study attempts to establish whether mergers carried out between Spanish agrifood cooperatives during the period 1995-2005 have contributed to reaching some of the objectives they were set out to achieve: improving the economic-financial situation of the companies involved, increasing income and reducing costs. To do so, mergers that took place during this period were analyzed in four autonomous communities (Andalusia, Navarra, La Rioja and the Basque Country). Despite the considerable variability observed following the time-based analysis of the economic-financial situation of cooperatives prior to and after merger, statistically significant differences were only found in four of the fifteen variables studied. These were operating profit (a 99% reduction), financial income (an increase of 240%), extraordinary income (400% increase) and cost of goods sold (16% reduction), of all of which are calculated with respect to production value. The results obtained generally indicate that the objectives that were originally the motivation for initiating the merger processes have not been reached, as the financial situation of the cooperatives has not, by and large, undergone any significant improvement, nor have average unit costs been reduced. Performance and profitability have not improved either and the firms involved have found themselves at lower levels than the average for the sector.